HUBUNGAN KESIAPAN INSTITUSI DENGAN KELULUSAN MAHASISWA D3 KEPERAWATAN DALAM MENGHADAPI EXIT EXAM - Rina Delfina; Maiyulis Maiyulis; Samwilson Slamet (Jurnal Vokasi Keperawatan (JVK), 2021)
Abstract Competency testing is carried out as a form of maintaining the quality of graduates who have competencies in accordance with nationally established standards. The exit exam can simply be interpreted as a graduation exam, meaning that if a student is unable to meet the pass mark from the exam, he or she is declared not to have passed the nursing education. The purpose of this study was to see the relationship between institutional readiness and passing the exit exam of D3 nursing students. This study uses an analytical survey with a cross sectional study approach. Collecting data using a questionnaire in the form of google form. Sampling was done by simple random sampling with a total of 110 people. The results showed that there was no relationship between institutional readiness and graduation of D3 Nursing students in facing the exit exam with a fisher ecxact value = 0.589 > 005. It is hoped that there will be synergy between institutions, lecturers and students in preparation for the UKOM exit exam by discussing more standardized questions. ukom, attend tutoring and take part in internal and external try outs.